290. Safety and Effectiveness of Oral Sodium Fusidate (Fusidic Acid) as Chronic Antibiotic Suppressive Therapy in Patients With Staphylococcal Bone or Joint Infections. (26th November 2018) - Sheets, Amanda; Graham, Donald; Darouiche, Rabih; Strayer, Andrew
Abstract: Background: Fusidic acid (FA) is an anti-staphylococcal agent used to treat chronic bone and joint infections (BJI) due to the availability of an oral formulation and its MRSA activity. Though used widely throughout the world for decades, FA is not approved in the USA. Methods: To evaluate the safety and effectiveness of FA as chronic suppressive therapy in patients with staphylococcal BJI, we enrolled 30 patients in a prospective, single-arm, multi-center study in the USA. Eligible patients had refractory infections that could not be managed surgically and/or had not responded to previous antibiotic treatment. In Part A of the study, all patients received 6 months of oral FA treatment. In the first 1–2 weeks, patients could receive a companion antibiotic. Clinical success was based on lack of need for surgery or additional antibiotics. After all patients completed Part A of the study, an interim analysis was performed. In Part B of the study (ongoing), patients who completed Part A and require continued suppressive therapy may continue to receive FA for a total of 24 months. Results: Most patients (83%) had orthopedic hardware infections. Therapy was considered successful at the 6-month visit in 18 patients (60%). Microbiological persistence was observed in eight patients, with three cases of decreasing FA susceptibility (including one case of resistance). Among 29 patients who experienced a treatment-emergent adverse event (TEAE), the most frequently reported events were: urinary tract infection ( n = 9), peripheral edema/swelling ( n = 8), nausea/dyspepsia ( n = 7). Seven patients experienced TEAEs related to study drug; mild gastrointestinal disorders were most common. Two treatment-related events (unrelated to therapeutic failure) led to discontinuation of study drug Conclusion: Patients with refractory BJI have few treatment options. In our study, 60% of infections were effectively suppressed for 6 months with FA treatment. The frequency of TEAEs was high, though not unexpected in this population with many chronic diseases. FA was well-tolerated with few patients experiencing treatment-related AEs leading to study drug discontinuation. FA administered chronically as monotherapy may lead to decreasing susceptibility and treatment failure in some patients; thus, combination therapy is warranted for this indication. Disclosures: A. Sheets, Melinta Therapeutics: Employee, Salary. D. Graham, Cempra: Grant Investigator, Research grant. R. Darouiche, Cempra: Grant Investigator, Grant recipient. A. Strayer, Melinta Therapeutics, Inc.: Employee and Shareholder, Salary.